Prevalence of extended-spectrum β-lactamase-producing Escherichia coli and residual antimicrobials in the environment in Vietnam. (18th April 2018) - Yamasaki, Shinji; Le, Tuyen Danh; Vien, Mai Quang; Van Dang, Chinh; Yamamoto, Yoshimasa
Abstract: Emergence and spread of antimicrobial-resistant bacteria, including extended-spectrum β-lactamase (ESBL)-producing Escherichia coli, have become serious problems worldwide. Recent studies conducted in Vietnam revealed that ESBL-producing E. coli are widely distributed in food animals and people. CTX-M-9 and CTX-M-1 are the most prevalent β-lactamases among the identified ESBLs. Furthermore, most of the ESBL-producing E. coli isolates were multi-drug resistant. Residual antimicrobials such as sulfamethoxazole, trimethoprim, sulfadimidine, cephalexin, and sulfadiazine were also detected at a high level in both animal meats and environmental water collected from several cities, including Ho Chi Minh city and Can Tho city. These recent studies indicated that improper use of antimicrobials in animal-originated food production might contribute to the emergence and high prevalence of ESBL-producing E. coli in Vietnam. Although clonal ESBL-producing E. coli was not identified, CTX-M-55 gene-carrying plasmids with similar sizes (105–139 kb) have been commonly detected in the ESBL-producing E. coli strains isolated from various food animals and human beings. This finding strongly suggests that horizontal transfer of the CTX-M plasmid among various E. coli strains played a critical role in the emergence and high prevalence of ESBL-producing E. coli in Vietnam.